THE MODERN VIEWS TO DIAGNOSIS OF KIDNEY DAMAGE IN PATIENTS WITH ARTERIAL HYPERTENSION FOR EARLY PREVENTION - Khimion, L.; Timoshchuk, L. (Ukrainian Journal of Nephrology and Dialysis, 2017)
The article discusses in detail the problem of the medico-social significance of early kidney damage in essential hypertension (EH) (according to the literature review and own research). Aim. To determine the prevalence of subclinical renal damage in the EAG of the first stage and to assess the diagnostic significance of the functional renal reserve (FRR). Materials and methods. A total of 70 patients were examined. The control group consisted of 50 people with established diagnosis of EH I stage, women - 20 (40%), mean age – 44,6±1,78 years, men - 30 (60%), average age – 46,57±2,23 years. The average duration of the EH is 3,5 ± 0,5 years. The control group included 20 practically healthy persons (11 women (55%), men - 9 (45%), average age 41,1 ± 1,96 years). All the patients underwent the following examinations: clinical examination, general clinical blood and urine tests, biochemical blood test (total protein, urea, creatinine, glucose, lipidogram) 24-hour BP monitoring, ECG, ECHO-CG, carotid ultrasound, definition FRR. The body mass index (BMI), the glomeru-laorpfhiltthratlimonosrcaotpey(aGnFdR) was calculated. Results. According to the FRR, the functional state of the kidneys significantly differs between subgroups of patients with EH stage I (p <0.05). In patients with the control group FRR - 62.14±10.60%, compared with patients with EH of the 1st subgroup – 23,31±4,9% and the 2nd subgroup - 10±3,02%. In patients of the 2nd subgroup of FRR, although within normal limits, it is noteworthy that it is located on the lower border. When performing the correlation analysis of the data of FRR and BP, the dependence was inversely proportional (r = -0.7, p <0.05). Conclusion. The eGFR was determined by the CKD-EPI formula in the examined patients with EH and control groups, which does not differ significantly. FRR in patients with EH I-II grade with the duration of the disease up to 5 years is significantly lower than in practically healthy peers; p <0.05. In patients with EH II grade (2nd subgroup) FNR more than twice as low as patients with EAG I degree; and is 10±3,2% and 23,3±4,9% respectively; p <0.05. Thus, according to the results of the study, it was found that FRR is a more sensitive indicator, which can help in the early diagnosis of kidney damage with EH.